Activated carbon for adsorption of per- and polyfluoroalkyl compounds in water samples
Patent Information
- Application Number
- JP2022138325
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-20
- Filing Date
- 2022-08-31
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2040-08-07
Smart Images

Figure 0007630146000001 
Figure 0007630146000002 
Figure 0007630146000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a per- and polyfluoroalkyl compound-adsorbing activated carbon for collecting per- and polyfluoroalkyl compounds contained in a water sample. [Background technology]
[0002] Per- and polyfluoroalkyl compounds are fluorine-substituted aliphatic compounds that have high thermal stability, high chemical stability, and high surface modification activity. Taking advantage of these properties, per- and polyfluoroalkyl compounds are widely used in industrial and chemical applications such as surface treatment agents, packaging materials, and liquid fire extinguishing agents.
[0003] Some per- and polyfluoroalkyl compounds are very stable chemical substances and are difficult to decompose under natural conditions after being released into the environment. For this reason, in recent years, per- and polyfluoroalkyl compounds have been recognized as persistent organic pollutants (POPs), and the production and use of perfluorooctane sulfonate (PFOS) (IUPAC name: 1,1,2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-heptadecafluorooctane-1-sulfonic acid) has been restricted since 2010 under the Stockholm Convention on Persistent Organic Pollutants (POPs Convention).
[0004] Perfluoroalkyl compounds have a completely fluorinated linear alkyl group and are substances represented by the chemical formula (i). Examples include perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) (IUPAC name: 2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-pentadecafluorooctanoic acid).
[0005]
number
[0006] Polyfluoroalkyl compounds are compounds in which some of the hydrogen atoms in an alkyl group have been replaced with fluorine, and are represented by the chemical formula (ii). For example, there are fluorotelomer alcohols.
[0007]
number
[0008] Thus, since per- and polyfluoroalkyl compounds continue to remain in nature (in water, soil, and air), the establishment of a quantitative test method for per- and polyfluoroalkyl compounds is being considered. The challenge in the study of a quantitative test method is the development of a collection material with high adsorption and desorption performance for per- and polyfluoroalkyl compounds. Water or air, which is a sample containing trace amounts of per- and polyfluoroalkyl compounds, is brought into contact with the collection material to collect the per- and polyfluoroalkyl compounds, and the compounds adsorbed by the collection material are desorbed in an extract by an extraction process and concentrated. After concentration, quantitative measurement is performed using an apparatus such as LC-MS / MS or GC-MS / MS, making it possible to measure the concentration of per- and polyfluoroalkyl compounds contained in the sample.
[0009] As an existing adsorption material, for example, an organic fluorine compound adsorbent made of cyclodextrin polymer has been proposed (Patent Document 1). This adsorbent is specialized for adsorption only and cannot desorb the compounds, so it is not suitable for use as an adsorption material used in quantitative measurement. In addition, cyclodextrin polymer is in powder or fine particle form, which makes it difficult to handle and has high resistance when passing liquid or air, resulting in problems such as the risk of fine powder leaking to the secondary side.
[0010] In addition, per- and polyfluoroalkyl compounds remain in the environment in various forms with a wide range of physicochemical properties, and existing adsorbents do not have sufficient collection performance, making it difficult to accurately quantitatively measure them.
[0011] The applicant therefore conducted further studies on the use of activated carbon as a collector for per- and polyfluoroalkyl compounds, and discovered that activated carbon makes it possible to collect per- and polyfluoroalkyl compounds, which contributes greatly to accurate quantitative measurement. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2012-101159 A Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention has been made in consideration of the above points, and in particular provides an activated carbon for adsorbing per- and polyfluoroalkyl compounds in a water sample, capable of capturing per- and polyfluoroalkyl compounds in the water sample, and a filter body using the same. [Means for solving the problem]
[0014] That is, 1 The invention is based on the BET specific surface area of the activated carbon adsorbent. 825~2017m 2 / g and the amount of surface oxide is 0.09~0.50meq / g Yes The sum of the micropore volumes of the activated carbon adsorbent having a pore diameter of 1 nm or less (V mic ) is 0.345~0.841cm 3 / g The present invention relates to an activated carbon for adsorbing per- and polyfluoroalkyl compounds in a water sample, characterized in that
[0015] No. 2 The invention is 1 The invention relates to an activated carbon for adsorbing per- and polyfluoroalkyl compounds in a water sample, wherein the activated carbon adsorbent is fibrous activated carbon.
[0016] No. 3 The invention is 1 or 2The present invention relates to a filter body for adsorbing per- and polyfluoroalkyl compounds in a water sample, the filter body comprising the adsorbent activated carbon of the present invention. Effect of the Invention
[0017] No. 1 According to the invention of the activated carbon for adsorbing per- and polyfluoroalkyl compounds in a water sample, the BET specific surface area of the activated carbon adsorbent is 825~2017m 2 / g and the amount of surface oxide is 0.09~0.50meq / g Yes The sum of the micropore volumes of the activated carbon adsorbent having a pore diameter of 1 nm or less (V mic ) is 0.345~0.841cm 3 / g This makes it possible to more efficiently collect the compound, which has been considered difficult to quantitatively measure until now.
[0018] No. 2 According to the invention, the per- and polyfluoroalkyl compound-adsorbing activated carbon in the water sample is 1 The invention To In the above, since the activated carbon adsorbent is fibrous activated carbon, the contact efficiency with per- and polyfluoroalkyl compounds is increased, and the adsorption performance can be improved.
[0019] No. 3 According to the invention, the per- and polyfluoroalkyl compound adsorption filter body in the water sample has the following characteristics: or 2 The invention of Since the adsorbent holds adsorbent activated carbon, it is possible to enhance the efficiency of collecting per- and polyfluoroalkyl compounds and also to provide good handling properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The activated carbon for adsorbing per- and polyfluoroalkyl compounds in water samples of the present invention is made of fibrous activated carbon or granular activated carbon. The fibrous activated carbon is activated carbon obtained by carbonizing and activating appropriate fibers, such as phenol resin-based, acrylic resin-based, cellulose-based, and coal pitch-based activated carbon. The fiber length, cross-sectional diameter, etc. are appropriate.
[0021] The raw materials for granular activated carbon include wood (scrap wood, thinned wood, sawdust), coffee bean residue, rice husks, coconut shells, bark, and fruit. These naturally derived raw materials are more likely to develop pores when carbonized and activated. In addition, since it is a secondary use of waste, it can be procured at low cost. Other raw materials that can be used include tires, petroleum pitch, burned synthetic resins such as urethane resin and phenolic resin, and even coal.
[0022] The activated carbon raw material is heated and carbonized at a temperature range of 200°C to 600°C as necessary to form micropores. The activated carbon raw material is then exposed to steam and carbon dioxide gas at a temperature range of 600°C to 1200°C for activation. As a result, activated carbon with various types of developed pores is produced. Other activation methods include activation with zinc chloride. Sequential washing is also performed.
[0023] The physical properties of the activated carbon thus produced determine the adsorption performance of the adsorbent. The adsorption performance of the activated carbon for adsorbing per- and polyfluoroalkyl compounds, which are the target adsorbents of the present invention, is determined by the specific surface area, which is an index showing the amount of pores formed in the activated carbon. In this specification, the specific surface area of each prototype is measured by the BET method (Brunauer, Emmett and Teller method).
[0024] The adsorption performance of activated carbon is also determined by the acidic functional groups present on the surface of the activated carbon. The acidic functional groups that increase due to surface oxidation of activated carbon are mainly hydrophilic groups such as carboxyl groups and phenolic hydroxyl groups. The acidic functional groups on the surface of activated carbon affect the collection capacity. The amount of these acidic functional groups can be understood as the amount of surface oxide.
[0025] In water, it is presumed that when the amount of surface oxides on activated carbon increases, the pores are blocked by water molecules that are firmly adsorbed to the surface functional groups by hydrogen bonds and the clusters of water molecules generated by this block the pores, preventing the physical access of the target adsorbate to the adsorption points (micropores).For this reason, it is believed that the smaller the amount of surface oxides on activated carbon, the better the adsorption performance of the target adsorbate.
[0026] As a method for reducing the surface oxides of the activated carbon, a known method such as heat treatment under an inert gas atmosphere can be used, and acidic functional groups such as phenolic hydroxyl groups and carboxyl groups on the surface of the activated carbon can be reduced.
[0027] Activated carbon is also defined by the pore size. In the case of an adsorbent such as activated carbon, there are micropores, mesopores, and macropores. The adsorption target and performance of activated carbon change depending on which range of pores is developed more. The activated carbon desired in the present invention is one that effectively adsorbs molecules of per- and polyfluoroalkyl compounds in a desorbable manner.
[0028] The adsorption performance of activated carbon to releasably adsorb per- and polyfluoroalkyl compounds in a water sample is, as will be explained in the Examples below, determined by a specific surface area of 800 m 2 This effect is exhibited by setting the surface oxide amount to 0.20 meq / g or more or the surface oxide amount to 0.20 meq / g or less. It is believed that the pores are blocked by the water molecules adsorbed by hydrogen bonds and the clusters of water molecules generated by the acidic functional groups present on the surface of the activated carbon, so that when the surface oxide amount is small, even activated carbon with a small specific surface area and a small number of pores can adsorb the compound to a certain degree. Conversely, even when the surface oxide amount is large and the adsorption of the compound into the pores is inhibited, activated carbon with a large specific surface area and a large number of pores can adsorb the compound to a certain degree or more.
[0029] In addition, if the specific surface area is equal to or greater than a certain level and the amount of surface oxide is equal to or less than a certain level, the per- and polyfluoroalkyl compounds in the water sample can be adsorbed in a more efficient and desorbable manner. 2 By making the surface oxide amount 0.50 meq / g or more and the surface oxide amount 0.50 meq / g or less, the adsorption performance of per- and polyfluoroalkyl compounds in a water sample can be further improved. EXAMPLES
[0030] [Activated carbon adsorbent used] The inventors used the following raw materials to prepare per- and polyfluoroalkyl compound-adsorbing activated carbon: · Fibrous activated carbon Futamura Chemical Co., Ltd.: Fibrous activated carbon "CF" (average fiber diameter: 15 μm) {Hereafter, this will be referred to as C1.} Futamura Chemical Co., Ltd.: Fibrous activated carbon "FE3010" (average fiber diameter: 15 μm) {Hereafter, this will be referred to as C2.} Futamura Chemical Co., Ltd.: Fibrous activated carbon "FE3012" (average fiber diameter: 15 μm) {Hereafter, this will be referred to as C3.} Futamura Chemical Co., Ltd.: Fibrous activated carbon "FE3013" (average fiber diameter: 15 μm) {Hereafter, this will be referred to as C4.} Futamura Chemical Co., Ltd.: Fibrous activated carbon "FE3015" (average fiber diameter: 15 μm) {Hereafter, this will be referred to as C5.} Futamura Chemical Co., Ltd.: Fibrous activated carbon "FE3018" (average fiber diameter: 15 μm) {Hereafter, this will be referred to as C6.} ·Granular activated carbon Futamura Chemical Co., Ltd.: Coconut shell activated carbon "CW480SZ" (average particle size: 250 μm) {Hereafter, this will be referred to as C7.}
[0031] [Examination of collection performance of per- and polyfluoroalkyl compounds in water samples 1] The inventors used the following prototype 1 to carry out trapping experiment 1 for per- and polyfluoroalkyl compounds in a water sample.
[0032] [Preparation of prototype] <Prototype 1> 10 g of fibrous activated carbon "FE3015" (C5) manufactured by Futamura Chemical was immersed in 500 ml of a 6% hydrogen peroxide solution, left to stand for 70 hours, then removed and dried to obtain the activated carbon of Prototype Example 1.
[0033] [Measurement of activated carbon 1] [Surface oxide amount] The amount of surface oxide (meq / g) was determined by applying the Boehm method, in which the adsorbent activated carbon of each example was shaken in a 0.05N aqueous solution of sodium hydroxide, filtered, and the filtrate was neutralized and titrated with 0.05N hydrochloric acid to obtain the amount of sodium hydroxide.
[0034] [BET specific surface area] Specific surface area (m 2 / g) was measured using an automatic specific surface area / pore distribution analyzer "BELSORP" manufactured by Microtrack BEL Corporation. - The nitrogen adsorption isotherm was measured at 77K using a "miniII" and calculated by the BET method (BET specific surface area).
[0035] [Average pore diameter] The average pore diameter (nm) is calculated by assuming that the pores are cylindrical and the pore volume (cm 3 / g) and specific surface area (m 2 / g) according to formula (iii).
[0036]
number
[0037] The physical properties of the activated carbon of Prototype 1 are shown in Table 1. From the top to the bottom of Table 1, the surface oxide amount (meq / g), BET specific surface area (m 2 / g), average pore diameter (nm), and average fiber diameter (μm).
[0038] [Table 1]
[0039] [Measurement of collection efficiency of per- and polyfluoroalkyl compounds in water samples 1] This time, fluorotelomer alcohols (hereinafter referred to as "FTOHs") were used as per- and polyfluoroalkyl compounds for the evaluation. FTOHs are substances represented by the above chemical formula (ii), and their names vary depending on the number of carbon atoms. For example, C8F 17 In the case of CH2CH2OH, it is named 8:2FTOH (IUPAC name: 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluoro-1-decanol).
[0040] Standard reagents for each FTOH of interest were added to ultrapure water to prepare a test solution of 0.5 ng / ml (0.5 ppb).
[0041] A 20 ml syringe was filled with 0.2 g of the fibrous activated carbon of Prototype Example 1, and 20 ml of the test solution was passed through it at a rate of 1 drop / second. After aeration and dehydration for 30 seconds, the adsorbent activated carbon in the syringe was thoroughly contacted and stirred with 15 ml of a mixed solvent mainly composed of dichloromethane and ethyl acetate, and then the solid-liquid separation was performed by centrifugation to collect the extract.
[0042] The extract was quantitatively measured in MRM mode using GC-MS / MS (Waters QuatrimicroGC) to confirm the collection performance.
[0043] Table 2 shows the recovery rate (%) of FTOHs for each target substance for the activated carbon of Prototype Example 1. The target substances are 4:2FTOH, 6:2FTOH, 8:2FTOH, and 10:2FTOH.
[0044] [Table 2]
[0045] [Study on collection performance of per- and polyfluoroalkyl compounds in water samples 2] Next, the inventors investigated PFOA (C8HF 15 O2) and PFOS (C8HF 17O3S), the following prototypes 2 to 13 were subjected to collection experiment 2 and evaluated.
[0046] [Preparation of prototype] <Prototype Example 2> 10 g of fibrous activated carbon "CF" (C1) manufactured by Futamura Chemical was used as the activated carbon of Prototype Example 2.
[0047] <Prototype 3> 10 g of fibrous activated carbon "CF" (C1) manufactured by Futamura Chemical was immersed in 500 ml of a 4.2% hydrogen peroxide solution, left to stand for 220 hours, then removed and dried to obtain the activated carbon of prototype 3.
[0048] <Prototype 4> 10 g of fibrous activated carbon "FE3010" (C2) manufactured by Futamura Chemical was used as the activated carbon of Prototype Example 4.
[0049] <Prototype 5> 10 g of fibrous activated carbon "FE3010" (C2) manufactured by Futamura Chemical was immersed in 500 ml of a 4.2% hydrogen peroxide solution, left to stand for 150 hours, then removed and dried to obtain the activated carbon of prototype 5.
[0050] <Prototype Example 6> 10 g of fibrous activated carbon "FE3012" (C3) manufactured by Futamura Chemical was used as the activated carbon of Prototype Example 6.
[0051] <Prototype 7> 10 g of fibrous activated carbon "FE3012" (C3) manufactured by Futamura Chemical was immersed in 500 ml of a 4.2% hydrogen peroxide solution, left to stand for 100 hours, then removed and dried to obtain the activated carbon of prototype 7.
[0052] <Prototype Example 8> 10 g of fibrous activated carbon "FE3013" (C4) manufactured by Futamura Chemical was immersed in 500 ml of a 1.5% hydrogen peroxide solution, left to stand for 70 hours, then removed and dried to obtain the activated carbon of prototype 8.
[0053] <Prototype Example 9> 10 g of fibrous activated carbon "FE3015" (C5) manufactured by Futamura Chemical was used as the activated carbon of Prototype Example 9.
[0054] <Prototype Example 10> 10 g of fibrous activated carbon "FE3015" (C5) manufactured by Futamura Chemical was immersed in 500 ml of a 1.5% hydrogen peroxide solution, left to stand for 40 hours, then removed and dried to obtain activated carbon for prototype 10.
[0055] <Prototype Example 11> 10 g of fibrous activated carbon "FE3015" (C5) manufactured by Futamura Chemical was immersed in 500 ml of a 4.2% hydrogen peroxide solution, left to stand for 70 hours, then removed and dried to obtain the activated carbon of prototype 11.
[0056] <Prototype Example 12> 10 g of fibrous activated carbon "FE3015" (C5) manufactured by Futamura Chemical was immersed in 500 ml of a 14.0% hydrogen peroxide solution, left to stand for 350 hours, then removed and dried to obtain the activated carbon of prototype 12.
[0057] <Prototype Example 13> 10 g of fibrous activated carbon "FE3015" (C5) manufactured by Futamura Chemical was immersed in 500 ml of a 18.9% hydrogen peroxide solution, left to stand for 480 hours, then removed and dried to obtain the activated carbon of prototype 13.
[0058] <Prototype Example 14> 10 g of fibrous activated carbon "FE3018" (C6) manufactured by Futamura Chemical was used as the activated carbon of Prototype Example 14.
[0059] <Prototype Example 15> 10 g of fibrous activated carbon "FE3018" (C6) manufactured by Futamura Chemical was immersed in 500 ml of a 4.2% hydrogen peroxide solution, left to stand for 50 hours, then removed and dried to obtain the activated carbon of prototype 15.
[0060] <Prototype Example 16> 10 g of fibrous activated carbon "FE3018" (C6) manufactured by Futamura Chemical was immersed in 500 ml of a 14.0% hydrogen peroxide solution, left to stand for 350 hours, then removed and dried to obtain the activated carbon of prototype 16.
[0061] <Prototype Example 17> 10 g of fibrous activated carbon "FE3018" (C6) manufactured by Futamura Chemical was immersed in 500 ml of a solution with a hydrogen peroxide concentration of 18.9%, left to stand for 480 hours, then removed and dried to obtain the activated carbon of Prototype Example 17.
[0062] <Prototype Example 18> 10 g of coconut shell activated carbon "CW480SZ" (C7) manufactured by Futamura Chemical was used as the activated carbon for Prototype Example 18.
[0063] [Measurement of activated carbon 2] The surface oxide, specific surface area and average pore diameter of Prototype Examples 2 to 18 were determined in the same manner as in "Measurement of Activated Carbon 1" above.
[0064] [Micropore volume] The pore volume was measured by nitrogen adsorption using an automatic specific surface area / pore distribution measuring device ("BELSORP-miniII", manufactured by Microtrack Bell Co., Ltd.). The sum of the micropore volumes (V mic )(cm 3 / g) was calculated by analyzing the dV / dD value in the range of pore diameters of 1 nm or less from the t-plot of the nitrogen gas adsorption isotherm using the MP method.
[0065] [Mesopore volume] The value of dV / dD in the range of pore diameters from 2 to 60 nm was analyzed by the DH method from the nitrogen gas adsorption isotherm. The diameter range of pore diameters from 2 to 60 nm in the analysis software is 2.43 to 59.72 nm. From the analysis results, the sum of the mesopore volumes (V met )(cm 3 / g) was calculated.
[0066] The physical properties of the activated carbons of Experimental Examples 2 to 18 are shown in Tables 3 to 5. In order from the top of Table 3, the surface oxide amount (meq / g), BET specific surface area (m 2 / g), average pore diameter (nm), micropore volume (V mic)(cm 3 / g), mesopore volume (V met )(cm 3 / g).
[0067] [Table 3]
[0068] [Table 4]
[0069] [Table 5]
[0070] [Measurement of collection efficiency of per- and polyfluoroalkyl compounds in water samples 2] The evaluation was carried out using PFOA and PFOS as per- and polyfluoroalkyl compounds.
[0071] Standard reagents for the target substances PFOA and PFOS were added to ultrapure water to adjust the solution concentration of PFOA and PFOS to 10 ng / ml (10 ppb) to prepare the test solution.
[0072] A 20 ml syringe was filled with 0.2 g of the above prototype, and 20 ml of the test solution was passed through it at a rate of 1 drop / second. After passing the solution through, the moisture in the activated carbon of the prototype in the syringe was removed by centrifugation. Then, 14 ml of a methanol solution adjusted to an ammonia concentration of 0.01% was used and passed through the dehydrated prototype at a rate of 1 drop / second to collect the extract.
[0073] The collected extract was concentrated to 1 ml using a nitrogen blowing concentrator, and then the extract was quantitatively measured in MRM mode using LC-MS / MS ("LCMS-8030", Shimadzu Corporation) to confirm the collection performance.
[0074] Tables 6 to 8 show the recovery rates (%) for each target substance for Prototype Examples 2 to 18. The target substances are PFOA and PFOS.
[0075] [Table 6]
[0076] [Table 7]
[0077] [Table 8]
[0078] [Results and Discussion] In prototypes 3 and 5, the recovery rate was low for both PFOA and PFOS, and the adsorption of the target substances was insufficient. It is presumed that the specific surface area was small and the amount of surface oxide was large, so that the pores capable of adsorbing the target substances were insufficient and the adsorption performance was not demonstrated.
[0079] In contrast, prototype 2, which has a small specific surface area, was able to adequately adsorb the target substance. This is thought to be because the amount of surface oxides was small, so water molecules were adsorbed by the functional groups on the activated carbon surface through hydrogen bonds, and the pores were less likely to be blocked by the clusters of water molecules generated as a result, and there were sufficient pores capable of adsorbing the target substance even though the specific surface area was small. This is thought to be why the adsorption performance of the activated carbon was well demonstrated.
[0080] It was also shown that the target substances were adsorbed in the prototypes 12, 13, 16, and 17, which had a large amount of surface oxide. This is thought to be because even if the amount of surface oxide was large and pores were blocked by water molecules or clusters, there were sufficient pores necessary for adsorption of the target substances because the specific surface area was large. Therefore, it is thought that the adsorption performance of the activated carbon was exerted and the adsorption performance of per- and polyfluoroalkyl compounds was demonstrated. From these, it can be understood that the conditions for ensuring the adsorption performance of per- and polyfluoroalkyl compounds in water samples are that the specific surface area is large or the amount of surface oxide is not more than a certain amount.
[0081] As can be seen from the results of Examples 9 to 13 and 14 to 17, which are examples in which the amount of surface oxide was changed using the same activated carbon, the adsorption performance of the examples in which the amount of surface oxide was increased by oxidation treatment tends to be inferior to the adsorption performance of the examples in which the amount of surface oxide was not increased or which were oxidized but had a small amount of surface oxide. Therefore, as described above, it can be understood that a small amount of surface oxide is preferable for the adsorption performance of per- and polyfluoroalkyl compounds in water samples.
[0082] Comparing the samples 2, 6, 9, and 14 with similar amounts of surface oxide, it was shown that when the specific surface area was above a certain level, the adsorption of per- and polyfluoroalkyl compounds in water samples was good. In particular, when the amount of surface oxide was small, the BET specific surface area was 800 m 2 / g or more, sufficient adsorption performance is exhibited, and when the amount of surface oxide is large, it is thought that a larger specific surface area tends to show better adsorption performance.
[0083] It was also shown that the adsorption performance of both PFOA and PFOS is further improved when the activated carbon has a large specific surface area and a small amount of surface oxide. It was found that by having a specific surface area larger than a certain level and a surface oxide amount smaller than a certain level, the adsorption performance of per- and polyfluoroalkyl compounds in water samples is further improved and a good recovery rate is shown. From the viewpoint of the contact efficiency between the target substance and activated carbon, it is thought that the use of fibrous activated carbon will enable more efficient adsorption of per- and polyfluoroalkyl compounds.
[0084] In addition, it is expected that if the activated carbon has developed micropores while satisfying the above conditions, the adsorption performance of per- and polyfluoroalkyl compounds in water samples will be further improved. It is also expected that if the mesopores are developed, the molecules of the target substance will be smoothly introduced into the pores of the activated carbon, and excellent adsorption performance will be exhibited. In addition, after the molecules of the target substance are adsorbed into the micropores, they will be easily desorbed out of the pores during the extraction operation, which is expected to result in a good recovery rate. [Industrial Applicability]
[0085] The activated carbon for adsorbing per- and polyfluoroalkyl compounds in water samples of the present invention can adsorb per- and polyfluoroalkyl compounds in water samples, making it possible to quantitatively measure the compounds, which was not possible with existing adsorption materials, and thus enabling effective quantitative evaluation of persistent organic pollutants.
Claims
1. The BET specific surface area of the activated carbon adsorbent is 825 to 2017 m 2 / g; The amount of surface oxide is 0.09 to 0.50 meq / g; The sum of the micropore volumes (V mic ) of the activated carbon adsorbent having pore diameters of 1 nm or less is 0.345 to 0.841 cm 3 / g. Activated carbon for adsorbing per- and polyfluoroalkyl compounds in a water sample.
2. The activated carbon for adsorbing per- and polyfluoroalkyl compounds in a water sample according to claim 1, wherein the activated carbon adsorbent is fibrous activated carbon.
3. 3. An adsorption filter body for per- and polyfluoroalkyl compounds in a water sample, comprising the adsorption activated carbon according to claim 1 or 2.
Citation Information
Patent Citations
Organic fluorine compound adsorbent
JP2012101159A
Activated carbon for water purifier, and activated carbon cartridge using the same
JP2013220413A
Method and system for treating and / or purifying water
WO2019063150A1